2004
DOI: 10.1002/pi.1540
|View full text |Cite
|
Sign up to set email alerts
|

Melting point depression and cocrystallization behavior of poly(ethylene‐co‐butylene 2,6‐naphthalate) copolymers

Abstract: The melting point depression and cocrystallization behavior of a series of random poly(ethylene‐co‐butylene 2,6‐naphthalate) P(EN‐co‐BN) copolymers were investigated using differential scanning calorimetry (DSC) and wide‐angle X‐ray diffraction (WAXD). These copolymers crystallize over the entire range of composition and they exhibit eutectic behavior. WAXD patterns showed that copolymers form exclusively poly(ethylene 2,6‐naphthalate) (PEN) type crystals or poly(butylene 2,6‐naphthalate) (PBN) type crystals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The higher the content of tBS, the lower the crystal regularity would be. 19,20,24,25 This could also be evidenced from the above WAXD study that the X c of copolyesters gradually declined with the consecutive increases in comonomer contents.…”
Section: ■ Results and Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The higher the content of tBS, the lower the crystal regularity would be. 19,20,24,25 This could also be evidenced from the above WAXD study that the X c of copolyesters gradually declined with the consecutive increases in comonomer contents.…”
Section: ■ Results and Discussionmentioning
confidence: 63%
“…It demonstrated that the practically incorporated content of tBS in the PBSdominant crystal was very less, and a majority of tBS was in an amorphous state. 20,25,35 The PBS crystal was more stable and compact, and it readily crystallized alone in a kinetically favorable manner. Thus, excess effort was required to receive the incorporated tBS unit.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The virgin hemp fibers were treated for an hour with 5N NaOH solution in order to increase their thermal stability based on an alternative to the procedure of K. Specht et al . The melting point depression of PET was achieved by blending with 5% (w/w) polycaprolactone in an internal batch mixer (Haake Rheomix, Polylab OS system), based on a previously published method by Papageorgiou et al . The compounding process of alkaline treated fibers and modified PET was done in an internal batch mixer (Haake Rheomix, Polylab OS system, USA), with the melting chamber heated at 250°C.…”
Section: Methodsmentioning
confidence: 99%
“…They have increasing slopes, indicating that it is easier to create the excess volume necessary for a comonomer unit in an already imperfect crystal lattice. [48][49][50] From the above analysis it is concluded that copolymer crystallization is expected to result in rejection of PSu from PESu crystals and enrichment of the amorphous phase in PSu units. This is most probably anticipated to affect biodegradation of the materials, as mainly the amorphous phase is affected by enzymes and also PPSu shows higher biodegradation rates.…”
Section: Thermodynamic Analysis Of the Melting Point Depressionmentioning
confidence: 99%